Phenolic acid content and antioxidative capacity of methanolic extracts from quality Indian mustard genotypes - H Punetha; Ankur Adhikari (Journal of Oilseed Brassica, 2026)
Brassica is one of the foremost oilseed crop cultivated in several parts of the world. Its oil is consumable and defattedmeal is a good element for use in aquaculture, animal and human diets, which acquires a copious amount of healthenhancingphytochemicals and anticarcinogenic compounds such as glucosinolates and antioxidative principles suchas phenolics, flavonoids, vitamin- C & E. The present investigation emphasized on the phenolic content and antioxidativeactivity in 30 germplasm of Brassica juncea. It is catechizing that methanolic extracts of a defatted meal of PRQ-2005-11(BE) (24.14 mg/ml) exhibit paramount in-vitro antioxidative property and F3-F4(3) (6.48 mg/g) possessed utmost totalphenolic content. Ortho dihidroxyphenol content differ from 0.070 mg/ml (LG 2005-36-1) to 0.323 mg/ml (F3-F4(2)). Thereducing power activity was observed to be highest in PLGM-2002-2-7(1.722) followed by PRQ-2005-11-BE (1.674 mg/ml), DCF4-F5-3 (1.672 mg/ml) in a dose-dependent manner. The predominant free radical-scavenging activity was observedin DCF4-F5(3) (84.27 mg/ml) at the concentration of 800 μg/ml. Whereas the heightened chelating activity was found inPRQ-2005-4(BL) (71.81 mg/ml) followed by PRQ-2004-9 (71.54 mg/ml) and PDLM 2003-9-6 (70.23 mg/ml) at the concentrationof 800 μg/ml. Thus the defatted meal of 30 Indian mustard genotypes was found to possess rich antioxidative capacitywhich further utilized in the preparation of functional foods as a viable food ingredient.